The 5-minute facial workout : 30 exercises for a naturally beautiful face - Pez, Catherine (Robert Rose, 2014)
How to combat the effects of aging in just 5 minutes a day. Each exercise has clear instructions, with photographs that demonstrate the movements, so performing each exercise is easy and straightforward.